Mechanisms underlying food-related symptoms in disorders of gut-brain interaction: Course ahead in research and clinical practice. (February 2023) - Colomier, Esther; Algera, Joost P.; Van den Houte, Karen; Simrén, Magnus; Tack, Jan
Abstract: A subgroup of patients with a disorder of gut-brain interaction (DGBI) report symptoms such as abdominal pain, gas-related symptoms, dyspeptic symptoms and loose stool or urgency after meal intake. Therefore, the effect of several dietary therapies including fibre-rich or restrictive diets have already been studied in patients with irritable bowel syndrome, functional abdominal bloating or distention, and functional dyspepsia. However, there is a paucity of studies in the literature on the mechanisms underlying food-related symptoms. Therefore, this review focuses on these potential mechanisms and explains the role of nutrient sensing and tasting, physical considerations, malabsorption or allergy-like reaction to food and its interaction with microbiota. In addition, it emphasizes the importance of future research and clinical practice regarding food-related symptoms in patients with a DGBI. Graphical abstract: Image 1